Encyclopedia of GIS 2017
DOI: 10.1007/978-3-319-17885-1_298
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionally Extended Nine-Intersection Model (DE-9IM)

Abstract: except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…To detect and compute SIFT descriptors, we used the OpenCV 2 library. Furthermore, we used the Shapely 3 package for Python to calculate concrete spatial relations between object-polygons in each scene, based on the DE-9IM model [23]. Moreover, for computing the optimal solution of an HC encoding, we utilized CLASP 3.1.2 and GRINGO 4.5.1 [7].…”
Section: Discussionmentioning
confidence: 99%
“…To detect and compute SIFT descriptors, we used the OpenCV 2 library. Furthermore, we used the Shapely 3 package for Python to calculate concrete spatial relations between object-polygons in each scene, based on the DE-9IM model [23]. Moreover, for computing the optimal solution of an HC encoding, we utilized CLASP 3.1.2 and GRINGO 4.5.1 [7].…”
Section: Discussionmentioning
confidence: 99%
“…If our focal data depict streets as line geometries, we can request which neighborhoods these streets intersect. Generally, there is a multitude of more possibilities of formulating such requests on georeferenced data (e.g., Strobl, 2017) that also depend on research questions within specific scientific disciplines as shown below.…”
Section: What Is Spatial Linking?mentioning
confidence: 99%
“…The Dimensionally Extended 9-Intersection Model (DE-9IM) (Strobl, 2008) is a full descriptive assertion about two spatial objects in 2 R . The "9-Intersection" model belongs to binary classification.…”
Section: The Dimensionally Extended Modelmentioning
confidence: 99%